Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41467-023-40802-z
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-envelope phase on-chip scanner and control of laser beams

Václav Hanus,
Beatrix Fehér,
Viktória Csajbók
et al.

Abstract: The carrier-envelope phase (CEP) is an important property of few-cycle laser pulses, allowing for light field control of electronic processes during laser-matter interactions. Thus, the measurement and control of CEP is essential for applications of few-cycle lasers. Currently, there is no robust method for measuring the non-trivial spatial CEP distribution of few-cycle laser pulses. Here, we demonstrate a compact on-chip, ambient-air, CEP scanning probe with 0.1 µm3 resolution based on optical driving of CEP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Interestingly, this measurement suggests a possible way to control the CEP evolution of a broadband laser pulse upon focusing. As shown in [ 22 ], by using spatial modulators, it is possible to engineer the waist (and therefore the Rayleigh range) of the different spectral components of the input laser beam, thus matching the value of g CEP to the specific needs of the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this measurement suggests a possible way to control the CEP evolution of a broadband laser pulse upon focusing. As shown in [ 22 ], by using spatial modulators, it is possible to engineer the waist (and therefore the Rayleigh range) of the different spectral components of the input laser beam, thus matching the value of g CEP to the specific needs of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the spatial dependence of the CEP becomes particularly relevant whenever the relative dimensions of beam and sample are such that the phase of the electric field cannot be considered uniform over the interaction area. Some experiments [ 16 ], [ 19 ], [ 20 ], [ 21 ], [ 22 ] have already investigated the CEP evolution of focused broadband pulses, showing nontrivial spatial profiles. In particular, it has recently been demonstrated that different parameters like chromatic aberrations and chirp can strongly affect the spatial variations of the CEP in the vicinity of the focus [ 22 ], [ 23 ], [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2(b,c). This highlights the exceptional properties of 2D materials for light-field control applications and marks them being suitable for CEP detecting applications as for example spatial 3D CEP scanning [23] or for nonlinear photoconductive sampling [13]. Here, the question arises: what is the mechanism of the ultrafast current generation in metals?…”
Section: Methodsmentioning
confidence: 99%
“…Our samples comprise alternating layers of iridium (Ir) metal and Al 2 O 3 dielectric, fabricated using the atomic layer deposition technique [22]. This material exhibits a high third-order nonlinear susceptibility and we have previously demonstrated its applicability in a CEP-scanning device for characterizing few-cycle laser beams [23]. Here, we establish a straightforward empirical relationship linking the measured current and the third-order nonlinear susceptibility.…”
Section: Introductionmentioning
confidence: 99%